MAPPING OF MANGROVE VEGETATION USING LANDSAT SATELLITE IMAGERYIN THE ESTUARY OF GANGSAL RIVER INDRAGIRI HILIR REGENCY RIAU PROVINCE - Susilo, Hendri; Galib, Musrifin; Mulyadi, Aras (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
The research was conducted in January - March 2019. This study aims to map and analyze changes in the area and density of mangrove vegetation based on NDVI values and community structure in the Muara Sungai Gangsal, Indragiri Hilir Regency. To analyze the area and density of NDVI using Landsat 5 TM satellite imagery in 2008 and Landsat 8 OLI/TIRS in 2018. Analysis using ArcGis 10.3 software. The calculation of mangroves based on community structure used the Transect Line Plot method at 6 stations for community structure sampling. The area of mangrove vegetation in 2008 was 2,706 ha and in 2018 it was 2,693 ha. The results of the analysis of mangrove vegetation area from 2008 to 2018 there was a reduction of 13 ha. The NDVI value for 2008 criteria is rarely 133 ha, while 2.009 ha are wide and 564 ha is dense. The NDVI value of the 2018 mangrove vegetation is rarely 16 hectares, while 2,135 hectares are in the area and 542 hectares are dense. Based on the analysis of mangrove density in 2018 at 6 sampling point stations ranging from 866 ind/ha to 1,522 ind/ha. Density criteria are rarely detected at station I with a density of 922 ind/ha and station II with a density of 866 ind/ha. The criterion of moderate density was detected at station V with a density of 1,255 ind/ha and station VI with a density of 1,044 ind/ha. Criteria for solid density were detected at station III with a density of 1,522 ind/ha and station IV with a density of 1,511 ind/ha